Using THIEVES Strategy to Improve the Seventh Grade Students’ Reading Comprehension Achievement - Cristya Larasati; Amalia Hasanah; Eka Sartika (Yayasan Karinosseff Muda Indonesia, 2023)
This research was conducted with the aim of finding out whether there is significant improvement on students’ reading comprehension achievement before and after being taught by using THIEVES strategy and there is significant differences on students’ reading comprehension achievement who are taught by using THIEVES strategy and those who are not. This research was conducted for 12 meetings and quasi-experimental research design was used to conduct the research. The population in this study were all seventh grade students of SMPN 1 Panang Enim. In selecting the sample the writer used purposive sampling technique and in this study the total sample was 62 which included the experimental class and controll class. To analyze the data the writer used paired sample t-test and independent sample t-test via SPSS 25. Based on the result of paired sample t-test, the p-output was 0.000 with df=30 (2.042), and t-output was 6.291. Since the p-output was lower than 0.05 and t-output was higher than t-table (2.042) therefore it can be concluded that there was significant improvement from students’ pre-test to post-test scores in experimental class taught by using THIEVES Strategy. And based on the result of independent sample t-test, the p-output was 0.002 with df=60 (1.671), and t-output was 3.212. Since the p-output was lower than 0.05 and the t-output was higher than t-table (1.671) therefore it can be concluded that that there was significant difference on students’ reading comprehension achievement who are taught by using THIEVES strategy and those who are not at SMPN 1 Panang Enim.